A systematic review of the biological, social, and environmental determinants of intellectual disability in children and adolescents - Leonard, Helen; Montgomery, Alicia; Wolff, Brittany; Strumpher, Elissa; Masi, Anne; Woolfenden, Susan; Williams, Katrina; Eapen, Valsamma; Finlay-Jones, Amy; Whitehouse, Andrew; Symons, Martyn; Licari, Melissa; et al. (Frontiers in Psychiatry, 2022)
Abstract AIM This systematic review aimed to identify the most important social, environmental, biological and/or genetic risk factors for intellectual disability. METHOD Eligible were published prospective or retrospective comparative studies investigating risk factors for intellectual disability in children 4 to 18 years. Exclusions were single group studies with no comparator without ID and a sample size < 100. Electronic databases (Medline, Cochrane Library, EMBASE, PsycInfo, Campbell Collaboration and CINAHL) were searched for eligible publications from 1980 and 2020. Joanna Briggs Institute critical appraisal instruments, appropriate for study type, were used to assess study quality and risk of bias. Descriptive characteristics and individual study results were presented followed by a synthesis for individual risk factors, also assessed using GRADE. RESULTS 58 individual eligible studies were grouped into six exposure topics; sociodemographic; antenatal and perinatal; maternal physical health; maternal mental health; environmental; genetic or biological studies. There were few eligible genetic studies. For half the topics the certainty of evidence (GRADE) was moderate or high. CONCLUSION Multiple studies have examined individual potential determinants of intellectual disability but few have investigated holistically to identify those populations most at risk. Our review would indicate there are vulnerable groups where risk factors we identified such as low socioeconomic status , minority ethnicity, teenage motherhood, maternal mental illness and alcohol abuse may cluster, highlighting a target for preventive strategies. At risk populations need to be identified and monitored so that interventions can be implemented when appropriate, at preconception, during pregnancy or after birth. This could reduce the likelihood of intellectual disability and provide optimal opportunities for vulnerable infants.